"Nigerium massiliense" gen. nov., sp. nov., a new bacterium isolated from the gut from a patient with acute malnutrition. (September 2016) - Traore, Sory Ibrahima; Brah, Souleymane; Delerce, Jeremy; Fournier, Pierre Edouard; Raoult, Didier; Edouard, Sophie
Abstract: We propose the main characteristics of a new bacterium named " Nigerium massiliense " strain SIT5 (CSURP1302) that was isolated from the stool of a 2-year-old Nigerian child suffering from kwashiorkor, a form of severe acute malnutrition.